Новий міжродовий гібрид ×Cydolus rudenkoana Mezhenskyj (Rosaceae Juss.) - Mezhenskyj, V.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2009)
The description of a new intergeneric hybrid Cydonia oblonga Mill. × Malus domestica Borkh. is given.